2012
DOI: 10.1152/ajpregu.00045.2012
|View full text |Cite
|
Sign up to set email alerts
|

Frog urinary bladder epithelial cells express TLR4 and respond to bacterial LPS by increase of iNOS expression andl-arginine uptake

Abstract: As in mammals, epithelium of the amphibian urinary bladder forms a barrier to pathogen entry and is a first line of defense against penetrating microorganisms. We investigated the effect of Escherichia coli LPS on generation of nitric oxide (NO), a critically important mediator during infectious processes, by primary cultured frog (Rana temporaria) urinary bladder epithelial cells (FUBEC). It was found that FUBEC constitutively express Toll-like receptor 4 (TLR4), a receptor of LPS, and respond to LPS (10 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…28 In frog, the TLR4 is respond to LPS as a receptor in urinary bladder epithelial cells. 29 As the pathway prediction, it showed that TLR4 might be failing to respond to LPS through LBP binding to CD14 induced the pathway. Hence, the fact that TLR4 of B. maxima can recognize the LPS to induce the pathway remains to be elucidated.…”
Section: Resultsmentioning
confidence: 96%
“…28 In frog, the TLR4 is respond to LPS as a receptor in urinary bladder epithelial cells. 29 As the pathway prediction, it showed that TLR4 might be failing to respond to LPS through LBP binding to CD14 induced the pathway. Hence, the fact that TLR4 of B. maxima can recognize the LPS to induce the pathway remains to be elucidated.…”
Section: Resultsmentioning
confidence: 96%
“…In amphibian immune studies, many of the genes known to be involved in mammalian innate immunity have been identified in X. laevis and Xenopus tropicalis (Robert and Ohta, 2009). In Xenopus species, inflammatory stimulation with bacteria and LPS induced increases in some important components (e.g., lectin, cytokines, nitric oxide, stress protein) of innate immune responses in various tissues and plasma (Cui et al, 2011;Morales et al, 2003;Nagata et al, 2013;Nikolaeva et al, 2012). However, few studies have examined the hormonal regulation of immune responses in amphibian leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ishii et al (2007) identified the putative TLR4, which is homologous to mammalian TLR4, from X. laevis. Furthermore, immunoblotting with TLR4 antibody demonstrated that the receptor expresses in frog leukocytes (Nikolaeva et al, 2012), although the function of the LPS receptor of the Xenopus TLR4 remains unclear. We also revealed that the UII-UTR system not only promoted the migration of monocytes and lymphocytes via the RhoA/Rho kinase signaling pathway but also upregulated the expression of some cytokine genes.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian urinary bladder and inner medulla collecting duct epithelial cells, active TLR4/CD14‐complexes and signaling cascade of LPS were revealed (Schilling et al, ; Chassin et al, ; Song et al, ; Schnerberich and Hartinger, ). In frog urinary bladder epithelial cells, TLR4 mediates LPS‐induced expression of iNOS, suggesting the involvement of NO in the suppression of bacterial growth (Nikolaeva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that R. temporaria urinary bladder epithelial cells are able to recognize bacterial LPS and to respond by TLR4 (toll‐like receptor 4)‐mediated increase of inducible NO‐synthase (iNOS) expression at the level of mRNA and protein, which appears to be a part of the innate immune response (Nikolaeva et al, ). The goals of the present work were to characterize the frequency of occurrence and pattern of Gram‐negative bacteria in urinary bladder tissue and isolated epithelial cells, and to study the relationship between the presence of bacteria in mucosal epithelium and AVT‐induced level of OWP.…”
mentioning
confidence: 99%